2017
DOI: 10.1093/heapol/czx180
|View full text |Cite
|
Sign up to set email alerts
|

Jeopardizing quality at the frontline of healthcare: prevalence and risk factors for disrespect and abuse during facility-based childbirth in Ethiopia

Abstract: Disrespect and abuse (D&A) experienced by women during facility-based childbirth has gained global recognition as a threat to eliminating preventable maternal mortality and morbidity. This study explored the frequency and associated factors of D&A in four rural health centres in Ethiopia. Experiences of women who delivered in these facilities were captured by direct observation of client-provider interaction (N = 193) and exit interview at time of discharge (N = 204). Incidence of D&A was observed in each faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
107
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 34 publications
23
107
2
1
Order By: Relevance
“…There was significant association found between D&A and the time of delivery (daytime or night) in this study as women who delivered at night reported less D&A than those who delivered in the day time. This is similar to the findings of Banks et al [ Banks et al, 2018] that women who delivered at night were less likely to report D&A than those who delivered during day, but the difference was not significant and Nawab et al report no variation with time of delivery [Nawab et al, 2019]. D&A was highest when delivery was at hospital (46.4%) and lowest when it was at a health center (25%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There was significant association found between D&A and the time of delivery (daytime or night) in this study as women who delivered at night reported less D&A than those who delivered in the day time. This is similar to the findings of Banks et al [ Banks et al, 2018] that women who delivered at night were less likely to report D&A than those who delivered during day, but the difference was not significant and Nawab et al report no variation with time of delivery [Nawab et al, 2019]. D&A was highest when delivery was at hospital (46.4%) and lowest when it was at a health center (25%).…”
Section: Discussionsupporting
confidence: 88%
“…As in previous study, the present study also showed that mothers who stayed in a health facility longer than 2 days after delivery were likely to experience D&A [17,18]. The present study findings also corroborate with previous studies that childbirth complications were associated with reporting D&A [Banks et al, 2018;Abuya, 2015]. The present study has shown that D&A was commoner among women with high monthly family income.…”
Section: When Women Experience Danda Their Relatives May Retaliatesupporting
confidence: 92%
See 1 more Smart Citation
“…Mistreatment ranges from subtle negligence and abandonment to overt verbal or physical abuse. The Bowser and Hill framework is commonly cited to describe aspects of mistreatment during childbirth (4,6,(8)(9)(10)(11)(12). These categories include physical abuse, non-consented care (including denial of birth companionship), non-con dential care, non-digni ed care (including verbal abuse), discrimination based on speci c attributes, abandonment or denial of care and detention in facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Respectful care is a fundamental right for every woman and baby (10). However, many women in Ethiopia are mistreated by their attendants during facility based childbirth (14)(15)(16)(17)(18)(19)(20)(21). This mistreatment is manifested by any form of uncaring behavior or inhumane treatment (22).…”
Section: Introductionmentioning
confidence: 99%